Determinants of farmers’ investment in soil conservation technologies in hill plantations - SUDHA, R.; SEKAR, C. (Journal of Soil and Water Conservation, 2021)
The study was conducted in the Nilgiris district of Tamil Nadu, where the problems of soil erosion were extensive. Multistage purposive sampling method was used to examine the financial feasibility and the factors influencing the investment of soil conservation technologies adopted by the farmers. In tea plantation, stone wall had the highest NPV of Rs.74335. The bench terrace had the highest Internal Rate of Return IRR of 34 % for carrot. The Net Present Value (NPV), Benefit Cost Ratio (BCR) and Internal Rate of Return (IRR) for both annual and perennial crops were found to be encouraging. In farmer’s investment analysis, change in one standard deviation in farm size leads to change in investment of Rs.9022 on soil conservation investment. Farmers’ education increasing the likelihood of investment in soil conservation. High cost of conservation technologies was the important constraints to farmers to adopt the soil conservation technologies.